2002
DOI: 10.1086/342911
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Hepatitis C Virus Is Influenced by Cytomegalovirus

Abstract: We investigated the effect of beta-herpesviruses on allograft failure and mortality, hepatitis C virus (HCV) replication, and liver histologic characteristics among 92 HCV-infected liver transplant recipients. Reactivation of cytomegalovirus (CMV) but not of human herpesvirus 6 (HHV-6) was independently associated with allograft failure and mortality (risk ratio, 3.71; 95% confidence interval, 1.64-8.39); allograft failure and mortality was observed in 48% of patients with CMV disease, 35% of patients with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
57
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 44 publications
6
57
1
Order By: Relevance
“…It has been demonstrated that CMV infection is associated with an increased risk of recurrent HCV hepatitis after transplantation. 41,42 As HHV-6 is similar biologically to CMV, HHV-6 infection might also be implicated in HCV recurrence after liver transplant. The present analysis suggests that HHV-6 is not involved in recurrence of HCV hepatitis after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CMV infection is associated with an increased risk of recurrent HCV hepatitis after transplantation. 41,42 As HHV-6 is similar biologically to CMV, HHV-6 infection might also be implicated in HCV recurrence after liver transplant. The present analysis suggests that HHV-6 is not involved in recurrence of HCV hepatitis after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CMV disease had a higher fibrosis stage and had a trend toward a higher hepatitis activity index and HCV load at 16 weeks after liver transplantation. 8 Interestingly, while both HHV-6 and CMV infection were common in this cohort, HHV-7 was not detected in the plasma of the patients. 8 This is similar to our finding of a lower rate of HHV-7 infection in the HCV-positive group vs. the HCV-negative group.…”
Section: Discussionmentioning
confidence: 63%
“…Some previous studies have suggested more rapid progression of HCV in liver transplant recipients coinfected with CMV or HHV-6. [7][8][9][10] Since viral interactions may be bidirectional, we evaluated whether HCV infection promoted herpesvirus replication using sensitive quantitative polymerase chain reaction assays. In this study of 177 liver transplant patients, there was no evidence for an immunomodulatory role for HCV with respect to herpesvirus reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations